Entrepreneurial Marketing and Performance of Small and Medium Scale Enterprises in Akwa Ibom State - Samuel G Etuk; Nse-Obong Augustine Udoh; Nfawa Erasmus Usani (International Journal of Entrepreneurship, Business, and Creative Economy, 2024)
Entrepreneurial marketing has become increasingly popular in the fields of entrepreneurship and marketing, as well as among organizations aiming to obtain a competitive edge. In practice, small and medium-sized enterprises (SMEs) in Akwa Ibom State, Nigeria, generally see entrepreneurial marketing as an appealing and efficient marketing strategy motivated by the desire to make the most of their unique strengths. These SMEs are involved in the sale of products and services. This study aimed to investigate the influence of entrepreneurial marketing on the performance of small and medium-scale enterprises in Akwa Ibom State. The sample size for the study was 400, determined using the Taro Yamane formula. The proxies for entrepreneurial marketing were considered jointly as customer orientation, entrepreneurial orientation, and innovation orientation. The researchers adopted a survey research design. A structured questionnaire was designed to obtain data from 400 SME owners. We also adopted a simple random technique for this study. We tested the combined hypothesis using multiple regression analyses. The study revealed a significant influence of customer orientation, entrepreneurial orientation, and innovation orientation on the performance of small and medium-scale enterprises in Akwa Ibom State. In conclusion, this study empirically provides evidence of the influence of entrepreneurial marketing on SME performance. SMEs can improve their performance by embracing the entrepreneurial marketing philosophy. Based on these conclusions and findings, the researchers recommended that SMEs in Akwa Ibom State improve their customer orientation to understand their customers better.